Development of tuneable green-to-red emitting transparent film based on Nafion with TbIII/EuIII β-diketonate complexes modulated by pH and proton flow. Issue 4 (12th June 2020) - Kamebuchi, Hajime; Yoshioka, Taiho; Tadokoro, Makoto
Abstract : Multicolour luminescence of a transparent emitter has been finely tuned through pH adjustment and external-voltage induced proton conduction in Nafion membrane. Abstract : Nafion membranes are recognised as cation exchangers and excellent proton conductors. Emissive Ln III -β-diketonate complexes, [LnIII2(PBA)6 ] (Ln = Eu, Tb; HPBA = N -(2-pyridinyl)benzoylacetamide), were incorporated into a transparent Nafion film. Upon incorporation, reversible emission by the green light emitter [TbIII2(PBA)6 ] and red light emitter [EuIII2(PBA)6 ] could be controlled through pH adjustment. [TbIII2(PBA)6 ] emitted only under acidic conditions, while [EuIII2(PBA)6 ] emitted only under basic conditions. Taking advantage of Nafion's high proton conductivity brought about dynamic changes in the wavelengths emitted by the film. When an in-plane external voltage was applied to the film, red wavelength emission appeared to migrate toward the negative electrode. Owing to the proton concentration gradient induced by the electric field, emission by Eu III at 615 nm was enhanced near the positive electrode, whereas proton deficiency suppressed emission by [TbIII2(PBA)6 ]. Tuneable emission in the transparent Nafion system enhances its potential for use as an energy-saving material.